2001
DOI: 10.1007/s004240100521
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of ATP on oxytocin-induced intracellular Ca2+ response in mouse mammary myoepithelial cells

Abstract: An increase in intracellular Ca2+ ([Ca2+]i) is essential for mammary myoepithelial cells to contract, leading to milk ejection during lactation. In this study, the intracellular signaling leading to the increase in [Ca2+]i in cultured myoepithelial cells from mouse lactating mammary glands was investigated using fura-2 fluorescence ratiometry. [Ca2+]i increased in cultured myoepithelial cells in response to either oxytocin (1 nM) or ATP (10 microM), and the cells then contracted. These [Ca2+]i responses were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…We postulate that this purinergic activation produces the cell contraction that we have observed. A similar mechanism has been reported in myoepithelial cells (19). The contraction profoundly alters the apical membrane topography with the loss of normal microvillar architecture.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…We postulate that this purinergic activation produces the cell contraction that we have observed. A similar mechanism has been reported in myoepithelial cells (19). The contraction profoundly alters the apical membrane topography with the loss of normal microvillar architecture.…”
Section: Resultssupporting
confidence: 69%
“…A known modulator of epithelial cell contraction is purinergic stimulation that acts by means of intracellular Ca 2ϩ elevation (19). As already discussed, others have demonstrated that hypotonic-induced sodium transport correlates with ATP release from epithelial cells into the basolateral compartment, and this acts via P2 receptors to stimulate a rise in intracellular Ca 2ϩ (8).…”
Section: Resultsmentioning
confidence: 94%
“…Although oxytocin is considered to be the most important trigger of contraction of MEC in response to suckling during lactation, MEC might also contract in the resting state following acetylcholine, 5-hydroxytryptamine, bradykinin, arginine-vasopressin and ATP treatment [Nakano et al, 2001]. Consequently, it seems reasonable that a counterregulation mechanism exists for the physiological reduction of the contractile tone in MEC in the lactating as well as in the resting mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic effects of ATP and oxytocin in increasing [Ca 2ϩ ] i in mouse mammary myoepithelial cells suggest that activation of purinergic receptors may facilitate myoepithelial cell contraction in the milk ejection response (Nakano et al, 2001). P2Y 2 receptors on apical and basolateral membranes appear to be involved (Blaug et al, 2003).…”
Section: Reproductive Systemmentioning
confidence: 99%